SAT0631 Lack of association between clinical and ultrasound measures of disease activity in rheumatoid arthritisclinical remission: a cross-sectional analysis. (12th June 2018) - Baker, K.F.; Thompson, B.; Lendrem, D.; Pratt, A.G.; Isaacs, J.D.
Abstract : Background: Ultrasound (US) measures of synovitis and tenosynovitis have been shown to persist in patients with rheumatoid arthritis (RA) who achieve clinical remission. Objectives: To assess the prevalence of such US findings in RA clinical remission, and analyse whether the US abnormalities found in this group of patients could be predicted by their clinical parameters. Methods: Patients with established RA (1987 or 2010 diagnostic criteria) in clinical remission (DAS28-CRP<2.4) on conventional synthetic disease-modifying anti-rheumatic drugs (DMARDs) were recruited as part of the Biomarkers of Remission in Rheumatoid Arthritis (BioRRA) Study. Patients who had received systemic glucocorticoids in the past 3 months were excluded. All patients underwent baseline clinical assessment followed by a 7-joint US scan (Backhaus et al). US assessment was performed by the same operator (KB) blinded to disease activity score. Synovial Power Doppler (SPD) and greyscale (SGS) change were measured using a 4-point semi-quantitative scale (0–3); tendon GS (TGS) and erosions were classified as either present 1 or absent (0). Intra- and inter-rater scoring agreement was good (Cohen's kappa 0.72 and 0.61 respectively). The association between individual dependent variables (SPD, SGS, TGS, and erosions) and clinical parameters was assessed by multivariate ordinal logistic regression, with Benjamini-Hochberg adjustment for multiple testing. Results: 66 patients with RA in remission (median disease duration 6 years, median age 66 years) were included in the analysis. US abnormalities were common in both DAS28-CRP and ACR/ EULAR 2011 Boolean remission (table 1). Seven associations were significant at the unadjusted p<0.05 level (figure 1). Only two associations remained statistically significant after multiple test correction, namely those of disease duration and TJC with higher and lower erosion scores respectively (table 2). Conclusions: We demonstrate considerable subclinical US findings in RA patients in clinical remission, even when remission is defined using the more stringent ACR/EULAR Boolean criteria. Patients with longer disease duration and fewer tender joints had more joint erosions, though no other significant associations were seen after multiple test correction. Most strikingly SPD, which portends a poor prognosis, failed to show significant association with any of the clinical parameters. Our results suggest that clinical and ultrasound examinations may serve complementary, rather than duplicative, roles in the assessment of RA remission. Reference: [1] Backhaus, et al. Arthritis Rheum;61:1194–201. Disclosure of Interest: None declared